2015
DOI: 10.3389/fmicb.2015.00750
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing celecoxib as a topical antimicrobial agent

Abstract: There is an urgent need for new antibiotics and alternative strategies to combat multidrug-resistant bacterial pathogens, which are a growing clinical issue. Repurposing existing approved drugs with known pharmacology and toxicology is an alternative strategy to accelerate antimicrobial research and development. In this study, we show that celecoxib, a marketed inhibitor of cyclooxygenase-2, exhibits broad-spectrum antimicrobial activity against Gram-positive pathogens from a variety of genera, including Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 61 publications
6
53
0
Order By: Relevance
“…All animal procedures were approved by the Purdue University Animal Care and Use Committee (West Lafayette, IN). An in vivo murine MRSA skin infection study was conducted as described elsewhere [2,22–24]. Briefly, mice (five mice per group) received an intradermal injection (40 μL) of MRSA USA300 containing 1.65 × 10 8 CFU.…”
Section: Methodsmentioning
confidence: 99%
“…All animal procedures were approved by the Purdue University Animal Care and Use Committee (West Lafayette, IN). An in vivo murine MRSA skin infection study was conducted as described elsewhere [2,22–24]. Briefly, mice (five mice per group) received an intradermal injection (40 μL) of MRSA USA300 containing 1.65 × 10 8 CFU.…”
Section: Methodsmentioning
confidence: 99%
“…The concept of drug repositioning has recently gained momentum and emerged as a viable approach to expedite anti-infective drug development (Butts and Krysan, 2012; Thangamani et al, 2015a,b,c). For example, several reports have demonstrated that auranofin, an orally bioavailable FDA-approved drug for treatment of rheumatoid arthritis, exhibits potent antibacterial and antiparasitic activities (Jackson-Rosario et al, 2009; Debnath et al, 2012; Cassetta et al, 2014; Hokai et al, 2014; Aguinagalde et al, 2015; Thangamani et al, 2016a,b).…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that individuals who take NSAIDs have a different bacterial profile compared to those who do not take NSAIDs (20). Celecoxib also has direct antimicrobial activity, although it is not clear whether its chemopreventive action is related to its effects on microbiota or the metabolites they produce (21, 22). …”
Section: Introductionmentioning
confidence: 99%